Cluster management synergy valuation: Synthesis and illustration of a discounted cash flow synergy valuation model for cluster management organisations - De Kock, Neil (Department of Finance and Tax, 2016)
The practice of cluster management has become an integral component to the modern cluster business environment. This research develops a framework for the valuation of synergies generated by a cluster management organisation (CMO) to be used as either a method of (ex-post) management evaluation or (ex-ante) for capital budgeting purposes. The theoretical framework is synthesised from clustering and business alliance (predominantly Mergers and Acquisitions (M&A) and Joint Ventures (JV)), literature. The case of the South African Furniture Initiative (SAFI) was used to inform model development and to illustrate practical application of the theoretical synergy valuation model. The case study found that the synergy valuation model faces problems with practical application due to the wide variety of activities commonly associated with CMO goals and objectives. It concludes that even though a synergy framework would provide a useful tool for evaluation and capital budgeting, further research is required to develop a more accurate method of impact estimation.